Acute liver injury induced by carbon tetrachloride reversal by Gandankang aqueous extracts through nuclear factor erythroid 2-related factor 2 signaling pathway - Wei, Yuan-yuan; Wang, Hui-ru; Fan, Yi-meng; Gu, Jin-hua; Zhang, Xiu-ying; Gong, Xu-hao; Hao, Zhi-hui (Ecotoxicology and environmental safety, 2023)
The aims of this study were to evaluated the effect and underlying mechanism of Gandankang (GDK) aqueous extract in alleviating the acute liver injury induced by carbon tetrachloride (CCl4) in vivo and in vitro. Mice were divided into 5 groups (n = 8) for acute (Groups: control, 0.3 % CCl4, BD (Bifendate), 1.17, 2.34 and 4.68 mg/kg GDK) liver injury study. 10 µL/g CCl4 with corn oil were injected interperitoneally (i.p) expect the control group. HepG2 cells were used in vitro study. The results showed GDK can effectively inhibit liver damage and restore the structure and function of the liver. In mechanism, GDK inhibited CCl4-induced liver fibrosis and blocked the NF-κB pathway to effectively inhibit the hepatic inflammatory response; and inhibited CCl4-induced oxidative stress by upregulating the Keap1/Nrf2 pathway-related proteins and promoting the synthesis of several antioxidants. Additionally, it inhibited ferroptosis in the liver by regulating the expression of ACSl4 and GPX4. GDK reduced lipid peroxide generation in vitro by downregulating the production of reactive oxygen species and Fe2+ aggregation, thereby inhibiting ferroptosis and alleviating CCl4-induced hepatocyte injury. In conclusion, we describe the potential complex mechanism underlying the effect of GDK against acute liver injury. [Display omitted] •Gandankang (GDK) ameliorated acute liver injury by mitigating hepatocyte apoptosis and inflammation.•Excessive ferroptosis, apoptosis and oxidative stress synergizes to cell death.•Nrf2 pathway is the key target of GDK in inhibiting liver injury.